Epitope characterization of anti-JAM-A antibodies using orthogonal mass spectrometry and surface plasmon resonance approaches. Issue 8 (17th November 2017) - Terral, Guillaume; Champion, Thierry; Debaene, François; Colas, Olivier; Bourguet, Maxime; Wagner-Rousset, Elsa; Corvaia, Nathalie; Beck, Alain; Cianferani, Sarah
ABSTRACT: Junctional adhesion molecule-A (JAM-A) is an adherens and tight junction protein expressed by endothelial and epithelial cells and associated with cancer progression. We present here the extensive characterization of immune complexes involving JAM-A antigen and three monoclonal antibodies (mAbs), including hz6F4-2, a humanized version of anti-tumoral 6F4 mAb identified by a functional and proteomic approach in our laboratory. A specific workflow that combines orthogonal approaches has been designed to determine binding stoichiometries along with JAM-A epitope mapping determination at high resolution for these three mAbs. Native mass spectrometry experiments revealed different binding stoichiometries and affinities, with two molecules of JAM-A being able to bind to hz6F4-2 and F11 Fab, while only one JAM-A was bound to J10.4. Surface plasmon resonance indirect competitive binding assays suggested epitopes located in close proximity for hz6F4-2 and F11. Finally, hydrogen-deuterium exchange mass spectrometry was used to precisely identify epitopes for all mAbs. The results obtained by orthogonal biophysical approaches showed a clear correlation between the determined epitopes and JAM-A binding characteristics, allowing the basis for molecular recognition of JAM-A by hz6F4-2 to be definitively established for the first time. Taken together, our results highlight the power of MS-based structural approaches for epitope mapping and mAb conformational characterization.